(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Takayasu's arteritis (TA) is a rare, systemic, chronic inflammatory arteriopathy of large and medium vessels. It affects women of reproductive age and causes narrowing, occlusion, and aneurysms of systemic and pulmonary arteries, especially the arch of the aorta and its branches. A can lead to an increased risk of cardiovascular complications and neurological manifestations especially during conception, further impacting both maternal and perinatal outcomes. Here, we are presenting a rare case of a TA in pregnancy in a 29-year-old primigravida with postpartum neurological sequelae, who was closely monitored and managed at our tertiary care centre and ultimately enjoyed a favourable outcome. We noted the importance of detailed history, pre-conceptional counselling, multi-disciplinary care, and prompt management at the tertiary care institute.